Contribuições da literatura de Monteiro Lobato: um estudo sobre a formação de leitores na perspectiva de docentes do Ensino Fundamental, anos iniciais, da Região Sudoeste do Paraná. - Hinterlang, Cristina (2012)
Reading, specially of the literary text, it is essential to child is in process of cognitive formation, and the school, that is considered ideal environment to practice and encourage the reading of literature, should be aware of the function that needs to execute to put into effect in the process of critical readers. In perspective, this thesis investigates how is putted into practice the reading promotion of the literary text in initials grades of Elementary School, aiming at the readers formation. Specifically, besides characterizing the profile of the teacher / mediator of reading, by considering that the personal experiences of these educators could interfere in the process of educating readers, though, it was possible to understand preferences and deepen knowledge about the concepts of reading and literature that permeate the teachers‟ work. Also, researches were made about teaching actions developed from the reading of Monteiro Lobato‟s texts in order to reflect on their reception in the school context, i.e., we sought to investigate the concrete use and contributions about lobatianos texts in teaching.It is possible to understand that the reading of the mentioned author‟s books is important because it allows discussion of essential topics in Brazilian universe, and mainly, in children's education universe. Since Lobato‟s narratives are endowed with playful and educational elements. It is known that the writer was an avid promoter of reading in the decades from 1920 to 1940, therefore, it is possible to believe that reading projects that address his literature can contribute, significantly, to the readers formation. As theoretical support, it was used contemporary authors of literary criticism in view from the Aesthetics of Reception, such as Jauss (2002) and Iser (2002), and authors from the Sociology of Reading as Candido (2006), Petit (2008) and Horellou-Lafarge e Segré (2010). It also refers to the principal authors of literary criticism focused on the Brazilian children's literature as Arroyo (1988), Zilberman (1982; 2009), Lajolo (1988; 2001), Coelho (1993), Aguiar (2008), entre outros. The theoretical discussions produced by these studious reveal the importance of literature for the individual and social development, showing thus the necessity for research to investigate its expression in the social environment. Thus, this thesis sought to reveal the facts of the reality through representative samples. As an instrument of data collection, questionnaires were filled with teachers of municipal schools belonging to Francisco Beltrão Center for Education, in southwest of Paraná. From the analysis of the data, it is possible to infer that teachers despite having, in general, professional, do not show necessary "enthusiasm" in relation to reading activities, leading to the adoption of practices that do not prioritize reading as an activity of enjoyment. Thus, there has been an emphasis on the basic aspects of teaching traditional, where the structural analysis of the language prevails over the aesthetic character of the text. However, it refers to Monteiro Lobato‟s work, the professionals are unanimous in recognizing his importance, that is the reason many they showed the contributions of lobatiana‟s literature in the process of educating readers, among them are: to stimulate the interest the reader through the text, draw attention to reading, but also, lead the reader to perform readings of other authors